2017
DOI: 10.1016/j.ejmech.2017.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of 5,6-diaryl-1,2,4-triazines hybrids as potential apoptosis inducers

Abstract: A series of 5,6-diaryl-1,2,4-triazines hybrids bearing a 1,2,3-triazole linker were synthesized by molecular hybridization strategy and evaluated for antiproliferative activity against three selected cancer cell lines (MGC-803, EC-109 and PC-3). The first structure-activity relationship (SAR) for these 5,6-diaryl-1,2,4-triazines is explored in this report with evaluation of 15 variants of the structural class. Among these chemical derivatives, 3-(((1-(4-fluorobenzyl)-1H-1,2,3-triazol-4-yl)methyl)thio)-5,6-diph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Bioisosterism is a useful strategy in rational drug design to improve pharmacodynamic or pharmacokinetic properties of lead compounds 20 . In order to optimise the reported colchicine site tubulin inhibitor 4 and discovery more potently anticancer agents [21][22][23][24][25] , benzothiazole was used as a bioisostere of the benzoxazole in the lead structure. Herein, we synthesised a variety of benzothiazole derivatives based on the lead compound 4 by the bioisosterism approach.…”
Section: Introductionmentioning
confidence: 99%
“…Bioisosterism is a useful strategy in rational drug design to improve pharmacodynamic or pharmacokinetic properties of lead compounds 20 . In order to optimise the reported colchicine site tubulin inhibitor 4 and discovery more potently anticancer agents [21][22][23][24][25] , benzothiazole was used as a bioisostere of the benzoxazole in the lead structure. Herein, we synthesised a variety of benzothiazole derivatives based on the lead compound 4 by the bioisosterism approach.…”
Section: Introductionmentioning
confidence: 99%
“…In addition it was indicated that alkylating activity increase with the number of 2-chloroethylamino groups [31]. It is interesting, that 1,3,5-triazine can modulate the functions: HIV-1 reverse transcriptase, estrogen receptor β (ΕRβ), glutathione S-transferase [38, 40]. 1,3,5-triazines with 2-chloroethylamino fragment can inhibit DNA replication, cell cycle arrest, induce of apoptosis and inhibit of cancer cells growth [31].…”
Section: Discussionmentioning
confidence: 99%
“…This characteristic types of cell death, are discussed in our previous paper [35]. Program cell death (PCD), also termed type 1 PCD, plays an important role in development of tissue homeostasis, degenerative diseases and cancer [40]. Apoptosis is a complex and multi-stage process.…”
Section: Discussionmentioning
confidence: 99%
“…All operations were carried out in accordance with the requirements of the cell cycle detection kit (Beyotime Biotechnology, Shanghai, China). The samples were analyzed by flow cytometer, and the data were analyzed by using the ModFit LT software (Verity Software House, Topsham, ME, USA) [59].…”
Section: Methodsmentioning
confidence: 99%